Report on the mineral statistics and mines of Newfoundland [electronic resource] - Howley, James P., 1847-1918.; Newfoundland. Geological Survey. ([St. John's, Nfld : s.n.], 1917)
Tables. Running title: Geological Survey of Newfoundland report for 1900. "For the year 1900." Electronic reproduction. Mode of access: Internet. 44